Species profiles life histories and environmental requirements of coastal fishes and invertebrates (North Atlantic)--Sea scallop - Mullen, Dennis M. (U.S. Department of the Interior, 1986)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.67)